Ecological and molecular mechanisms in plants to cope with environmental heterogeneity: a case study in Viola elatior - Schulz, Benjamin; Justus Liebig University Giessen (My University, 2015)
The ability to adjust to varying biotic and abiotic conditions is a key feature of plants to survive in an ever changing environment. In the course of evolution plants therefore have developed numerous mechanisms to cope with environmental heterogeneity and its unpredictability. This thesis investigates two of these mechanisms and their population ecological consequences in the cleistogamous species Viola elatior. The conducted studies intended to (1) extend our knowledge on the impact of epigenetic variation in environmental adjustment and (2) to investigate the population genetic effects of persistent soil seed banks under changing selection regimes and decreasing population size.

Die Fähigkeit, sich an variierende biotische und abiotische Bedingungen anzupassen, ist eine entscheidende Eigenschaft von Pflanzen, um in einer sich ständig verändernden Umwelt zu überleben. Im Laufe der Evolution haben Pflanzen daher eine Reihe von Mechanismen entwickelt, die helfen mit der Heterogenität und Unvorhersagbarkeit ihrer Lebensbedingungen zurechtzukommen. Die vorliegende Thesis untersucht zwei dieser Mechanismen und ihre populationsökologischen Folgen in der kleistogamen Pflanzenart Viola elatior. Ziel der durchgeführten Studien war es, eine besseres Verständnis über (1) den Einfluss epigenetischer Variabilität in Bezug auf Umweltanpassungen zu erlangen und (2) die populationsgenetischen Effekte von persistenten Samenbanken unter sich verändernden Selektionsregimen und sinkender Populationsgröße zu erforschen.
Keywords: Epigenetik; Viola; Samenbank; Umweltgradient; epigenetic; Viola; seed bank; environmental gradient; ddc:580